Monocyte Based Correlates of Immune Activation and Viremia in HIV-Infected Long-Term Non-Progressors - Prabhu, Varsha M.; Singh, Amit Kumar; Padwal, Varsha; Nagar, Vidya; Patil, Priya; Patel, Vainav (Frontiers in Immunology, 2019)
Abstract Background Disease progression monitoring through CD4 counts alone can be inadequate in HIV infection as ongoing immune activation may result in Serious Non-AIDS Events (SNAEs). SNAEs involve monocyte activation driven chronic inflammation with significant sequelae observed even during HAART. Here, we attempted to delineate functional monocyte based signatures across stages of HIV disease progression. Methods Participants spanning four cohorts were recruited - pre-ART (PA; <7 years of infection; n=20), long term non-progressors (LTNP; >7 years of infection, CD4>350 cells/µL, n=20), individuals on therapy (ART; n=18) and seronegative controls (SN; n=15). Immunophenotyping of monocyte subsets and evaluation of expression of HIV-binding receptors - CD4 & CCR5, marker of immune activation- HLA-DR and M2 phenotype - mannose receptor (CD206) was followed by association of monocyte-specific parameters with conventional markers of disease progression such as absolute CD4 count, CD4/CD8 ratio, viral load and T cell activation. Results A significant expansion of intermediate monocytes (CD14++CD16+) with a concomitant decline in classical subset (CD14++CD16-) was observed in all infected cohorts compared to seronegative controls. In addition, an expansion of the non-classical subset (CD14+CD16++) was observed in long term non-progressors. Dysregulation in monocyte subsets associated with CD4 count and CD4/CD8 ratio in PAs but not in LTNPs. We report for the first time that expression of CD206 is most prominent on intermediate monocytes which also have the highest expression of CD4, CCR5 and HLA-DR. Despite preserved CD4 counts, LTNPs had similar immune activation profiles to PAs, as evidenced by elevated HLA-DR expression across monocyte subsets. HLA-DR expression, similar to that in SNs, observed in the ART group indicated partial immune restoration within the monocyte compartment. Increased CD206 expression on monocytes together with frequency of activated CD4+ T lymphocytes (HLA-DR+CD38+) showed significant and positive association with viral load in LTNPs, but not PAs. Conclusion Our results describe for the first time the presence of monocyte dysregulation involving increased activation in LTNPs, who, in spite of preserved CD4 counts, may remain susceptible to prolonged effects of systemic inflammation and highlight CD206, as a unique non-T correlate of viremia, in viremic non-progression.